Aroma profiles and non-destructive determination of quality parameters of Japanese plums (Prunus salicina Lindl.) - Louw, Esme Denise (Stellenbosch : University of Stellenbosch, 2011)
Thesis (PhD(Agric) (Horticulture))--University of Stellenbosch, 2011.